Management of Educational Facilities and Infrastructure for Hygiene and Health Care in the Covid-19 Pandemic Era - Aminatul Fikriyah; Ahmad Royani (The Faculty of Education and Teaching Training, 2022)
Facilities and infrastructure are one of educational means for the implementation of the learning process to achieve educational goals effectively and efficiently. During a pandemic, it is necessary to provide infrastructure for hygiene and health care. This article aims to describe the planning, implementation, and evaluation of educational facilities and infrastructure for hygiene and health care during the Covid-19 pandemic era at SMP Negeri 01 Kencong. This study uses qualitative research methods with the type of narrative research. The results of this study include: 1) the Planning stage for the management of educational facilities and infrastructure for hygiene and health care in the Covid-19 pandemic era was done through needs analysis, projected needs, and socialization of the spread of Covid-19 conducted by MUSPIKA (Subdistrict Leadership Consultation) Kencong; 2) the Implementation of management of educational facilities and infrastructure for hygiene and health care in the era of the Covid-19 pandemic involved some process like procurement, distribution, inventory, maintenance, storage, and elimination of educational facilities and infrastructure for hygiene and health care; 3) the Evaluation of the management of educational facilities and infrastructure for hygiene and health care in the era of the Covid-19 pandemic was done through verbal evaluation and written evaluation. Sarana dan prasaran merupakan salah satu penunjang terselenggaranya proses pembelajaran untuk mencapai tujuan pedidikan secara efektif dan efisien. Pada masa pandemi, perlu pengadaan sarana prasana di bidang kebersihan dan kesehatan. Tujuan penulisan artikel ini adalah untuk mendeskripsikan perencanaan, pelaksanaan serta evaluasi sarana dan prasarana pendidikan di bidang kebersihan dan kesehatan pada era pandemi Covid-19 di SMP Negeri 01 Kencong. Penelitian ini menggunakan metode penelitian kualitatif dengan jenis penelitian naratif. Adapun hasil dari penelitian ini, di antaranya: 1) Perencanaan manajemen sarana dan prasarana pendidikan di bidang kebersihan dan kesehatan pada era pandemi Covid-19 meliputi analisis kebutuhan, proyeksi kebutuhan serta sosialiasasi penyebaran Covid-19 yang dilakukan oleh Musyawarah Pimpinan Kecamatan Kencong; 2) Pelaksanaan manajemen sarana dan prasarana pendidikan di bidang kebersihan dan kesehatan pada era pandemi Covid-19 meliputi pengadaan, penyaluran, inventarisasi, pemeliharaan, penyimpanan dan penghapusan sarana dan prasarana pendidikan di bidang kebersihan dan kesehatan; 3) Evaluasi manajemen sarana dan prasarana pendidikan di bidang kebersihan dan kesehatan pada era pandemi Covid-19 meliputi evaluasi secara lisan dan tertulis.